MENTAL HEALTH IN THE EASTERN MEDITERRANEAN REGION: FOCUS ON WOMEN, CHILDREN, THE ELDERLY AND REFUGEES - Niaz, Unaiza (Journal of Pakistan Psychiatric Society, 2022)
The Eastern Mediterranean Region (EMR) has some of the world’s poorest health metrics among the WHO regions. It has the highest prevalence of mental disorders worldwide. This is largely attributable to the region’s ongoing persistent humanitarian crises, which from one perspective, increase the need and demand for mental health services, while on the contrary eroding the capacity of health and social care systems to provide the basic care. With insufficient human, structural, institutional, data and financial resources, these mental health care systems continue to suffer from neglect and apathy. The situation is exacerbated further by the stigma, discrimination, and human rights’ violations that people with mental illnesses face, where women, children, the elderly, and immigrants are the highly susceptible population groups. This paper aims to outline the issues and risks linked with mental health in the Eastern Mediterranean Region, and also to provide practical and equitable recommendations that seek to address the past indifference and neglect in order to advocate the importance of mental health in public health.